Lesion of leukocytes, erythrocytes, and mesothelial cells by the coelomic fluid of Eisenia foetida earthworms - Rossmann, P; Bilej, M; Tucková, L; Starý, V; Kofronová, O (Folia microbiologica, 1997)
Coelomic fluid of Eisenia foetida earthworms is known to exert strong proteolytic, hemolytic, bacteriostatic, and cytolytic properties. Ultrastructural observations revealed that coelomic fluid causes multiple ruptures and defects in the erythrocyte membrane as well as in the membrane of murine peritoneal leukocytes. Incubation of peritoneal cells in coelomic fluid resulted in a disorganization of the macrophage surface microvilli, changes in the organization of cytoplasmic organelles and disruption and degranulation of mast cells. Severe mesothelial damage was observed after intraperitoneal administration of the coelomic fluid.
Keywords: Oligochaeta; tělesné tekutiny; Mitochondria; Body Fluids; epitelové buňky; peritoneum; Mast Cells; Peritoneal Cavity; peritoneální makrofágy; Epithelial Cells; Digestive System; myši inbrední BALB C; peritoneální dutina; ovce; Sheep; Mice, Inbred BALB C; leukocyty; Animals; ženské pohlaví; injekce intraperitoneální; Injections, Intraperitoneal; zvířata; mastocyty; Leukocytes; erytrocyty; myši; Erythrocytes; Macrophages, Peritoneal; Microvilli; Mice; Female; mikroklky; Peritoneum; mitochondrie; trávicí systém